A formação continuada e as práticas docentes com o uso do software GeoGebra - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Taking into account that, currently, Digital Technologies are increasingly occupying a prominent place in the teaching of school content, in particular, in the teaching of Mathematics, the GeoGebra software, the study deals with the Continuing Education of Mathematics teachers and has as its object of study the Processes of mathematical practices with the use of GeoGebra software, from a Continuing Education. Thus, it seeks to find an answer to the following question: What are the contributions of continuing education in the teaching and learning process with the use of GeoGebra Software? Therefore, we aim to know the processes of teaching practices with the use of Geogebra Software from a Continuing Education. This research on Mathematics Education, Continuing Education, Professional Development of Teachers and Digital Technologies in Mathematics Teaching has its theoretical bases in the light of D'Ambrósio (2013), Marcelo García (1999), Imbernón (2006), Borba (2019), Basniak (2014), among others. This is a research with a Qualitative approach, of the Case Study type, based on Yin (2014; 2016) and Ponte (2006), set in two state schools in Manacapuru (AM) and had as participants two Mathematics teachers. The collection of information was carried out through the Formative Path, using narrative interviews, via WhatsApp and Google Meet. For data analysis we used the narratives arising from the empirical process. This time, the analysis categories were based on the ideas put forward by Imbernón (2006), taking into account the recurring keywords in the transcribed narratives of the teachers participating in the research. Among the results obtained, in relation to the use of Digital Technologies in schools, we highlight the lack of an adequate environment, the need for equipment, internet and others. About the learning constituted in the course for the pedagogical didactic use of Digital Technologies in the school context, we emphasize GeoGebra, as a tool that, through the guidance of the teachers, aroused the interest of students and enabled learning. And also, the experience of teachers in Continuing Education raised new knowledge related to Professional Development as a permanent process throughout their professional life, based on reflections on their pedagogical practice.
Continuing education and teaching practices with the use of GeoGebra software
Keywords: Matemática - Estudo e ensino; GeoGebra (Software); Tecnologia Educacional - Manacapuru (AM); CIENCIAS HUMANAS: EDUCACAO: ENSINO-APRENDIZAGEM: METODOS E TECNICAS DE ENSINO; CIENCIAS HUMANAS: EDUCACAO: ENSINO-APRENDIZAGEM: TECNOLOGIA EDUCACIONAL; Formação continuada; Ensino de matemática; Tecnologias digitais; Software GeoGebra